HISTOLOGICAL AND BIOCHEMICAL EVALUATION OF WOUND REGENERATION POTENTIAL OF TERMINALIA CHEBULA FRUITS - S, KIRUBANANDAN; Ravi, Bharathi; S, Renganathan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The objective of this investigation was to evaluate the histological and biochemical evaluation of wound healing potential of the ethanol extract of Terminalia chebula fruits. Antibacterial activity and in vivo wound healing properties of the ethanol extract on infected lesions by reference strains of Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 in Wistar rats were investigated. A total of 32 rats were divided into two groups such as control group and Group treated with an extract of T. chebula. Control groups infected, but not treated with any medicine. The ethanol extract has a real healing potential and antibacterial activity against reference strains used. In addition, Histological analysis of Granulated tissue from treated group confirmed the regeneration of dermal wound with well-formed dermis and epidermis in the skin and then a tight bundle of synthesized collagen in the tissue. Therefore, these antibacterial properties and wound healing activities engage T. chebula in the process of developing an improved traditional medicine as alternative for existing therapy. Keywords: Wound infection, In vivo studies, Masson's trichrome staining and collagen.